Transformasi Digital Penyelenggaraan Rapat Umum Pemegang Saham Perseroan Terbatas - Ikhsan Lubis (Universitas Medan Area, 2021)
This study aims to see the development of Digital Transformation as the application of digital technology related to changes in interaction patterns in all aspects of human life, and the development of the cyber notary concept is no exception. The legal validity of electronic documents was further strengthened by the issuance of Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Electronic Information and Transactions. This research is a normative juridical research and analytical descriptive using a statutory approach, a conceptual approach, and a case approach. Data analysis was carried out qualitatively. The results of the study indicate that the legal validity of the notarial deed at the GMS of a Limited Liability Company through teleconference with electronic media where it is mandatory to use an affirmation mechanism and/or other procedures that provide the intent and purpose of the signing to be bound in an electronic transaction. As for the deed of the GMS teleconference, it is classified as a relaas deed and based on the provisions of the relaas deed, the notary's statement is in the form of a deed (the validity of the teleconference GMS can be ascertained).